White Noise e Cosmopolis: análise do processo de desumanização em ficções pós-modernas - Marques, Ana Carolina dos Santos [UNESP] (2014)
This study aims at analyzing the novels White Noise (1985) and Cosmopolis (2003), written by Don DeLillo, in order to examine the narrative strategies present in these postmodern fictions and verify the author’s approach concerning issues related to the power of capital, technology and the environment as well as to show his fierce criticism towards the dominant economic system. Taking these aspects into account, there will be a comparison on how these aspects are also noticed in Brazil at the present moment. Through the story of Jack Gladney, a professor of Hitler Studies, and his family, the book focuses on important characteristics of American society such as the influence of the media that transforms facts in great spectacles to be experienced at the same time around the globe. Jack’s family life changes completely after the Airborne Toxic Event, since this situation throws into question values related to privacy and ethics. In Cosmopolis, the narrative happens in one day. The protagonist, Eric Packer, is a young billionaire from the business world, who lives in a forty-eight room apartment in the highest building of New York City. One morning in April, he decides to go out for a haircut. In this “marathon” to his goal, many events happen inside and outside his limousine. Cosmopolis warns the readers about the critical stage of capitalism and its possible failure. This study will explore how the Brazilian society, due to new financial opportunities, becomes similar to the American society, such as an intense consumerism, the lack of values and the dehumanization. The discussion will be based on theorists such as Connor (1992), Eco (1986), Harvey (1989), Jameson (1997), Baudrillard (1988)